PENGGUNAAN SOFTWARECUTVIEWER MILL UNTUK MENINGKATKAN KETERAMPILAN DAN HASIL BELAJAR MATA DIKLAT CNC DASAR TU-3A KELAS XI PROGRAM KEAHLIAN TEKNIK PEMESINAN DI SMK NEGERI 2 SURAKARTA TAHUN PELAJARAN 2014/2015 - Yuliyanto, Rahmat Cahyo (Jurnal Nosel, 2015)
The aim of this research is to improve the skill and learning result in the Basic CNC TU-3A of the students in class XITechnical Machinery B of State Vocational High School 2 Surakarta in Academic Year 2014/2015. The target of change are improving students? skill and learning result, withaction variable is the uses CutViewer Millsoftware.This research is classroom action research with two cycles. Each cycle consisted of four phases, namely: planning, implementation, observation, and reflection. The subjects of this research were all of students as many as 31 from the class XITechnical Machinery B of State Vocational High School 2 Surakarta in Academic Year 2014/2015. The research conducted collaboration between researcher, subject matter teacher, observer, and students. The data of theresearch were collected through observation, documentation, test, and in-depth interview. The instrument validated whit content validity of theobservation sheet and expert judgment of the test.Data analyzed by descriptive comparative method and crictical analysis.The result shows that the usesCutViewer Millsoftware can improve the skill and learning result. In Cycle I, the average of student?s skill attainment is 65.42% and the average score is 80.91 with the percentage of the students who fulfill the minimum learning completeness criterion is 74.19%. In Cycle II, the student?s skill becomes 88.45% and the average score is 85.69, with the percentage of the students who fulfill the minimum learning completeness criterion is 100%.